Guest Editorial: Selected Papers from the 12th Conference of the European Association for the Teaching of Academic Writing - Anson, Chris M.; Benetos, Kalliopi; Devitt, Ann; Rapp, Christian (Journal of Academic Writing, 2025)
The guest editors of this special issue of the Journal of Academic Writing present a selection of papers from the 12th Conference of the European Association for the Teaching of Academic Writing, held at Zurich University of Applied Sciences in Winterthur, Switzerland, on 5–‍7 June, 2023.